Educulture Entrepreneurship As An Innovation To Improve The Quality Of Education: An Analysis Of Achieving Sustainable Development Goals (SDGs): Condition of Education in Indonesia, Educulture Entrepreneurship, Improving Quality Education Through Educulture Entrepreneurship Analysis of SDGs - Atikoh, Nurul; Isro'iyah, Latifatul; Rohim, Achmad Roysul; Ahsan, Nashrulloh (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Education is a complex and continuous process that involves the transfer of knowledge, skills, values and culture from one generation to the next. The teaching and learning process is an investment in character building, creativity and leadership. Education is also a major milestone in shaping the entrepreneurial character of students based on innovation by utilizing local wisdom. Local wisdom itself has not been fully developed and well managed, especially local wisdom in remote and underdeveloped areas. Education in Indonesia is currently facing a number of challenges that can affect the effectiveness of the education system as a whole. Some of the problems that can be identified are the existence of educational inequality in various regions, the high unemployment rate after graduating from school, the lack of educators, the lack of learning materials at school, and the immature character education of students. This writing aims to find out and explain how the Educulture Entrepreneurship strategy in improving the quality of education in Indonesia is analyzed from the Sustainable Development Goals. The research method used is descriptive-qualitative research with data collection techniques in the form of interviews, observations, and literature studies from several sources of books and relevant scientific articles. The result of this research is that collaboration between education, local wisdom, and entrepreneurship is an effective way to improve the quality of education in Indonesia. Through an educational innovation program with the theme of Educulture Entrepreneurship, namely conducting an Indramayu mango development project. This can be an educational curriculum development, developing PjBL-based learning projects, developing creative, innovative, and collaborative learning, empowering research-based local wisdom, developing MSME products, creating sustainable entrepreneurial opportunities, creating educational tourism for junior and senior high school students, providing training for students, and can be a forum for empowering local communities to the creation of IPR.